Electrochemical performance of Mo2C@PtRu synthesized by electrochemical deposition method on methanol oxidation - Nestor, Uwitonze; Chen, Wei; Chen, Yan-Xia (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The electrodeposition of Platinum and Ruthenium nanoparticles into Molybdenum carbide/ glassy carbon electrodes and their catalytic activity for the oxidatlon of methanol are described. These Mo2C@PtRu electrodes exhibit good activity with respect to the catalytic oxidation of methanol. The electrodes exhibited excellent long term stabilty in the acidic methanol solutions.